Hard Infrastructure as Local Economic Development (LED) Enabling Environment in Selected Local Governments in Aichi Prefecture, Japan - Marjorie D. Resuello (Intermestic: Journal of International Studies, 2018)
The study identified the Local Economic Development enabling environment to support small and medium enterprises (SMEs) in Aichi Prefecture, Japan. It employed participant observation research method in the national, regional, prefectural, city, and town governments, academic and research institutions, SMEs, chamber of commerce, business associations, and communities’ levels in Aichi Prefecture. The study revealed that Japanese government provides business support for SMEs as the force behind an economy with thriving SMEs industry. The support to hard infrastructure was identified as LED enabling environment fostering connectedness, innovation and value creation for SMEs’ attraction, growth, and global expansion. This is common among the selected local governments towards building up local competitiveness, addressing job and wealth creation, and promoting liveability through hard infrastructure development. The LED in Japan can be applied as a model for developing countries, especially in the ASEAN Region, in addressing poverty reduction and wealth creation.